Willingness to Pay For Achieving Good Status Across Rivers in the Republic of Ireland - Buckley, Cathal; Howley, Peter; O'Donoghue, Cathal; Kilgarriff, Paul (The Economic and Social Review, 2016)
The Water Framework Directive mandates EU Member States to achieve good status across all surface waters. Derogations from this have to be proven based on infeasibility or disproportionate cost. This study explores public preference for water quality objectives and assesses willingness to pay (WTP) for achieving good status across all rivers in the Republic of Ireland using contingent valuation. Mean WTP for achieving full good status across rivers was estimated at €19 per respondent per annum. WTP was influenced by social class, subjective perceptions relating to household financial status, education, recreational use, environmental values and river basin district.